Inovasi desain kemasan eco-friendly menggunakan coreldraw 22: studi kasus pada kantin man 1 pasuruan - GHOFUR, MUHAMMAD ABDUL (Maliki Interdisciplinary Journal, 2026)
This study aims to develop environmentally friendly packaging designs for the MAN 1 Pasuruan Canteen using CorelDRAW 2022 software. This approach is based on the 3R (Reduce, Reuse, Recycle) sustainability principle and aims to reduce the use of single-use plastic packaging through educational visual innovations. The research methods involved literature analysis, field observation, and 3D simulation-based digital design exploration. The results show that the use of recycled paper and efficient structural design reduced waste by up to 35% and saved 20% in production energy. The integration of educational visual elements such as 3R symbols and ecological colors significantly increased students’ environmental awareness. CorelDRAW proved to be effective in supporting design process efficiency, strengthening creativity, and integrating ecological messages through packaging media. This study confirms that packaging design not only serves to protect products but also becomes a means of education and behavioral transformation towards a sustainable lifestyle.